Study on Modification of SiO2 Thin Film Surface Morphology and Its Electrical Performance - Liu, Xiang; Liu, Hui (Asian Journal of Chemistry, 2014)
Silicon dioxide thin film was prepared by thermal growth method and PMMA film layer was prepared by spin coating. Silane coupling agent octadecyltrichlorosilane (OTS) be used to modified the surface of SiO2. The result of atomic force microscope (AFM) showed that using PMMA and OTS modified SiO2 layer can effectively improve the surface flatness and reduce the surface energy. The PMMA insulating layer reduces the contact barrier between the organic semiconductor insulating layer and the growth of thin films of copper phthalocyanin became more consistent. Compare with the single SiO2 insulation layer, thin film transistor devices on SiO2/PMMA and SiO2/OTS compound insulation layer with improved carrier mobility and lower threshold voltage. Experimental results showed that using double insulation layer structure can effectively improve the performance of organic thin film transistor.